2014
DOI: 10.1136/annrheumdis-2014-eular.5983
|View full text |Cite
|
Sign up to set email alerts
|

FRI0193 Herpes Zoster Infection across Auto-Immune and Inflammatory Diseases: Implications for Vaccination: Table 1.

Abstract: Background More than one million herpes zoster (HZ) cases occur in the United States every year. Currently, the live zoster vaccine is recommended for healthy older patients age ≥60 years. Whether the absolute risk for younger patients who have autoimmune or inflammatory conditions might be high enough to warrant vaccination of younger patients with these diseases is unclear. Objectives To evaluate the overall and age-stratified absolute incidence of HZ infections associated with different autoimmune and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Such patients should receive 1 dose of the shingles vaccine at least 14 days before initiation of immunosuppressive therapy. A study of patients with various autoimmune diseases compared with two cohorts of patients, one with diabetes and the other one with healthy controls, showed that the age-specific rates of HZ for patients with RA or SLE ≥ 40 years of age were greater than the corresponding rates in healthy individuals > 60 years old [77]. Given these elevated rates at baseline and that the vaccine is licensed for use in those aged 50 and older [78], we advocate administration of the vaccine in all patients with rheumatic diseases once they reach the age of 50 as long as no contraindications are present.…”
Section: Vaccination and Other Prevention Strategiesmentioning
confidence: 99%
“…Such patients should receive 1 dose of the shingles vaccine at least 14 days before initiation of immunosuppressive therapy. A study of patients with various autoimmune diseases compared with two cohorts of patients, one with diabetes and the other one with healthy controls, showed that the age-specific rates of HZ for patients with RA or SLE ≥ 40 years of age were greater than the corresponding rates in healthy individuals > 60 years old [77]. Given these elevated rates at baseline and that the vaccine is licensed for use in those aged 50 and older [78], we advocate administration of the vaccine in all patients with rheumatic diseases once they reach the age of 50 as long as no contraindications are present.…”
Section: Vaccination and Other Prevention Strategiesmentioning
confidence: 99%
“…По данным J. R. Curtis и соавт. [30], частота Herpes zoster (HZ) у больных СКВ и РА старше 40 лет превышает таковую среди здоровых лиц старше 60 лет -14,1, 7,5 и 3,0 на 1000 пациентолет, соответственно, при этом наиболее уязвимыми являются больные старше 50 лет. Согласно ретроспективному продольному когортному исследованию, проведённому американскими авторами, частота HZ в когорте больных РА превышала таковую в общей популяции (21,5 и 7,6 на 1000 пациенто-лет, соответственно).…”
Section: вакцинация против опоясывающего герпесаunclassified
“…По сравнению с общей популяцией, все больные АВРЗ (включая СКВ) имеют повышенный риск развития HZ. Анализ крупной базы данных показал, что скорректированные показатели частоты HZ среди больных СКВ превышали таковые у здоровых лиц -14,1 и 3,0 на 1000 пациенто-лет соответственно [35]. При проспективном анализе когорты больных СКВ риск развития HZ составил 1,7 (95% ДИ 1,08-2,71) [36].…”
Section: Herpes Zosterunclassified